Impaired Social Cognition in Epilepsy: A Review of What We Have Learnt From Neuroimaging Studies - Ives-Deliperi, Victoria Lyn; Jokeit, Hennric (Frontiers in Neurology, 2019)
Background: Social cognition refers to specific mental processes that subserve social interaction. Impaired social cognition has been increasingly reported in patients with epilepsy and impacts negatively on overall quality of life. In this article, we will review neuroimaging studies of social cognition in people with epilepsy. Method: An electronic search of the literature was conducted and 14 studies qualified for inclusion in the review. Results: Although the studies reviewed revealed a varied pattern of neural activations in response to emotion recognition and theory of mind tasks, consensual findings included altered pattern of signal activation in the social cognition network in patients with mesial temporal lobe epilepsy compared to healthy controls and significantly reduced signal activations and functional connectivity within this network in patients with right mesial temporal lobe pathology. Conclusion: This review contextualises our current understanding of the pathophysiology of impaired social cognition in epilepsy and makes recommendations for further research.